44.9k views
2 votes
I NEED HELP PLEASE, THANKS! :)

I NEED HELP PLEASE, THANKS! :)-example-1

2 Answers

4 votes

Answer:

x = 124

Explanation:


6 + \sqrt[5]{249 - 2x} = 7 \\ \sqrt[5]{249 - 2x} = 7 - 6 \\ \sqrt[5]{249 - 2x} = 1 \\ {\sqrt[5]{249 - 2x} }^(5) = {1}^(5)


249 - 2x = 1 \\ - 2x = 1 - 249 \\ - 2x = - 248 \\ ( - 2x)/( - 2) = ( - 248)/( - 2)


x = 124

I NEED HELP PLEASE, THANKS! :)-example-1
I NEED HELP PLEASE, THANKS! :)-example-2
User Hillin
by
4.0k points
3 votes

Answer:

124

Explanation:

First subtract 6 to both sides.


\sqrt[5]{249-2x} = 1

Then take the 5th power of both sides to remove the radical.


249-2x=1^5

Which is essentially:

-2x = 1 - 249

-2x = -248

Divide both sides by -2

x = 124

And there ya go :)

User Harsh Dattani
by
4.4k points